The Potential Advantages of Nanoparticle Drug Delivery Systems in Chemotherapy of Tuberculosis - Gelperina, Svetlana; Kisich, Kevin; Iseman, Michael D; Heifets, Leonid (American journal of respiratory and critical care medicine, 2005)
Nanoparticle-based drug delivery systems have considerable potential for treatment of tuberculosis (TB). The important technological advantages of nanoparticles used as drug carriers are high stability, high carrier capacity, feasibility of incorporation of both hydrophilic and hydrophobic substances, and feasibility of variable routes of administration, including oral application and inhalation. Nanoparticles can also be designed to allow controlled (sustained) drug release from the matrix. These properties of nanoparticles enable improvement of drug bioavailability and reduction of the dosing frequency, and may resolve the problem of nonadherence to prescribed therapy, which is one of the major obstacles in the control of TB epidemics. This article highlights some of the issues of nanotechnology relevant to the anti-TB drugs.